Mineralocorticoid receptor activation is crucial in the signalling pathway leading to the Anrep effect - Caldiz, Claudia Irma (2011)
The increase in myocardial reactive oxygen species after epidermal growth factor receptor transactivation is a crucial step in the autocrine/paracrine angiotensin II/endothelin receptor activation leading to the slow force response to stretch (SFR). Since experimental evidence suggests a link between angiotensin II or its AT1 receptor and the mineralocorticoid receptor (MR), and MR transactivates the epidermal growth factor receptor, we thought to determine whether MR activation participates in the SFR development in rat myocardium. We show here that MR activation is necessary to promote reactive oxygen species formation by a physiological concentration of angiotensin II (1 nmol l⁻¹), since an increase in superoxide anion formation of ~50% of basal was suppressed by blocking MR with spironolactone or eplerenone. This effect was also suppressed by blocking AT1, endothelin (type A) or epidermal growth factor receptors, by inhibiting NADPH oxydase or by targeting mitochondria, and was unaffected by glucocorticoid receptor inhibition. All interventions except AT1 receptor blockade blunted the increase in superoxide anion promoted by an equipotent dose of endothelin-1 (1 nmol l⁻¹) confirming that endothelin receptors activation is downstream of AT1. Similarly, an increase in superoxide anion promoted by an equipotent dose of aldosterone (10 nmol l⁻¹) was blocked by spironolactone or eplerenone, by preventing epidermal growth factor receptor transactivation, but not by inhibiting glucocorticoid receptors or protein synthesis, suggesting non-genomic MR effects. Combination of aldosterone plus endothelin-1 did not increase superoxide anion formation more than each agonist separately. We found that aldosterone increased phosphorylation of the redox-sensitive kinases ERK1/2-p90RSK and the NHE-1, effects that were eliminated by eplerenone or by preventing epidermal growth factor receptor transactivation. Finally, we provide evidence that the SFR is suppressed by MR blockade, by preventing epidermal growth factor receptor transactivation or by scavenging reactive oxygen species, but it is unaffected by glucocorticoid receptor blockade or protein synthesis inhibition. Our results suggest that MR activation is a necessary step in the stretch-triggered reactive oxygen species-mediated activation of redox-sensitive kinases upstream NHE-1.